Effect of pyraclostrobin on mulberry leaves nutrients, silkworm cocoon production and silk fiber performance - Ferreira, Saulo Rocha; Silva, Luiz Eduardo; Dos Santos, Renata Daniel; Filho, Romildo Toledo; Gomes, Otavio Fonseca Martins; Tonoli, Gustavo Henrique Denzin; Nicodemo, Daniel [UNESP] (FapUNIFESP (SciELO), 2021)
The present work evaluates the effect of pyraclostrobin fungicide on the nutritional quality of mulberry leaves, silkworm cocoon production and silk fiber mechanical performance. The evaluation was performed in two consecutive years. In Spring 2015, mulberry plants were treated twice with 4 doses of pyraclostrobin (0, 100, 200, and 300 g.ha-1), 30 and 15 days before pruning of the branches. In Spring 2016, the same plants received the same doses of pyraclostrobin only 30 days before pruning of the branches. Fifth instar caterpillars were fed on treated mulberry leaves. The mineral content of mulberry leaves was determined on pruning day of the branches and 30 days before. The consumption of mulberry leaves and the mortality rate of the caterpillars fed with the treated leaves was verified, and the cocoons obtained were classified and weighed. Silk fibers were submitted to mechanical evaluation by tensile test. Morphological and physical modification were evaluated by Scanning Electron Microscope (SEM) and X-ray diffraction (XRD). In 2015, the mortality of caterpillars fed on leaves treated with pyraclostrobin was at least 26.7% higher than the control. At 2016 even with a single application the weight of the cocoons was lower. The main variation in the mineral content was observed in Mn and Fe nutrients. Mineral intake had a noticeable effect in both crystallinity and tensile strength. Results show that the use of pyraclostrobin may reduce the mechanical behavior of silk thread up to 70%, indicating that its use is not indicated for mulberry planting aiming silk feeding.
Keywords: Bombyx mori; Fibroin changes; Mulberry leaves; Silk fibers; Silkworm mortality, fiber performance